Fenologia e componentes de rendimento de pessegueiro em condições subtropicais - Scariotto, Silvia (2011)
Peach tree, a specie from temperate climate, modify the phenology when cultivated at subtropical climate locations. The knowledge about local microclimate conditions and its influence on peach tree blooming and leafing, endodormancy overcoming, phenology and productive behavior is fundamental to achieve a successful implantation of adapted cultivars at the region. Therefore, the objective of this work was to obtain a better understanding about the behavior of genotypes of low and medium chilling requirements at subtropical climate location, with variable winters and risks of frost occurrence during bloming and fructification period. In the first chapter the sprouting ability of genotypes and development of productive branches (brindila formation) were studied in 34 genotypes within four years of evaluation (2007 to 2010). In the second chapter flowering, fruit set and the productive ability of genotypes were evaluated in 30 peach tree genotypes within three years (2008 to 2010). In the third and last chapter quality traits of fruits were evaluated in 29 genotypes of peach tree within the harvests from 2008 to 2010 and the evaluation about preference of fruits from some selected genotypes were also performed. The following analysis were performed: beginning of budburst and flowering (5% of open buds); full flowering (50% of open buds); leaf and flower buds density; percentage of leaf and flower budbrake ; percentage of bearing shoots formations (one-year-old or productive shoots) at 45 days after the end of leafing; fruit set between 30 and 35 days after blooming; yield (kg plant-1); mean weight of the fruit (g); diameter (mm); flesh firmness (N); total soluble solids (SST); total titrable acidity (ATT); pH; SST/ATT ratio and the preference of the consumer. Temperatures below 7.2°C and 12°C, and above 20°C, from May to August, as well as the occurrence of frost were recorded. Analysis of adaptability and stability were performed by GGE methodology (genotype main effect plus genotype by environment interaction effect), through biplot graphics. The genotypes Bonão, Rubimel, Santa Áurea, Libra, Kampai, Conserva 655 and Âmbar presented high percentages of budburst and development of bearing shoots and were kept stable for both traits within the evaluated years. Genotypes Santa Áurea, Cascata 1055, Conserva 1223, Conserva 977 Conserva 681, Cascata 1065, Conserva 871, Cascata 1070 and Cascata 967 presented the higher means of fruit set. Genotypes Conserva 681, Atenas, Kampai, Cascata 967, Conserva 977 and Conserva 655 presented better adaptability and higher crops. Genotypes of late blooming have higher stability of fruit set. Genotypes Rubimel, Cascata 1055, Cascata 587, Kampai, Cascata 1065 and Cascata 967 presented the best results for SST, ATT, pH and SST/ATT ratio, determining excellent quality of fruits for in natura consumption. Genotypes Atenas, Bonão, Libra, Âmbar, Conserva 844, Conserva 1127 and Santa Áurea presented good results for fruits destined to canning industry. Genotypes Conserva 985, Santa Áurea, Conserva 1127, Conserva 977, Rubimel, Cascata 1063 and Conserva 688 presented the higher mean weights of fruits. Sweet flavor fruits are preferred by the local consumers. Considering all analysis performed, the best genotypes were: Libra, Tropic Beauty, Bonão, Kampai, Cascata 967, Rubimel, Cascata 1055, Santa Áurea and Conserva 844.